Strategi Pemasaran Untuk Meningkatkan Penjualan Paket Wedding di The Ritz-Carlton, Bali - Ni Luh Risma Saputri; Ketut Arjaya; Luh Putu Citrawati (Journal of Event and Convention Management, 2022)
Besides its fame as a MICE events destination, Bali is also widely chosen by tourists to celebrate weddings, because Bali has various types of wedding venues equipped with numerous facilities. The emergence of the COVID-19 pandemic at the beginning of 2020 has affected every country all around the globe, including Indonesia; it has created significant damage to Indonesia's tourism sector, especially Bali. The descriptive analysis technique used by the author is the 7P of marketing (product, place, price, promotion, people, process, and physical evidence) and SWOT analysis (strength, weakness, opportunity, threat. As a result of this study, there are four marketing mix strategies to increase the sales of wedding packages in the COVID-19 era at The Ritz-Carlton, Bali. SO strategy CHSE certified company equipped with promotion of wedding package that is adjustable per clients' request and price flexibility in the midst of a global pandemic. ST strategy circles on increasing and creating new product variations of the wedding packages offered by improving the quality of the product and establisihing market segmentation in accordance with the COVID-19 situation and the company’s supporting facilities. WO strategy demands the business to optimize the utilization of technology and various platforms available to facilitate company’s activity through the internet, such as virtual venue tour.Last but not least, WT strategy concerns in improving the quality both in terms of wedding services and other service quality available in the hotel.